2022
DOI: 10.1037/emo0000876
|View full text |Cite
|
Sign up to set email alerts
|

Big smile, small self: Awe walks promote prosocial positive emotions in older adults.

Abstract: Aging into later life is often accompanied by social disconnection, anxiety, and sadness. Negative emotions are self-focused states with detrimental effects on aging and longevity. Awe-a positive emotion elicited when in the presence of vast things not immediately understood-reduces self-focus, promotes social connection, and fosters prosocial actions by encouraging a "small self." We investigated the emotional benefits of a novel "awe walk" intervention in healthy older adults. Sixty participants took weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 60 publications
3
49
0
Order By: Relevance
“…Evidence suggests that spending time in nature can promote overall self-reported wellbeing, for example, White et al (2019) found that people who spend at least two hours per week in nature are more likely to report higher wellbeing than those who do not spend any time in nature. Exposure to natural environments has also been found to increase positive and self-transcendent emotions such as awe (Sturm et al, 2020), peak experiences (Wulff and Maslow, 1965) and the perception feeling worthwhile (White et al, 2017).…”
Section: Connecting To Naturementioning
confidence: 99%
“…Evidence suggests that spending time in nature can promote overall self-reported wellbeing, for example, White et al (2019) found that people who spend at least two hours per week in nature are more likely to report higher wellbeing than those who do not spend any time in nature. Exposure to natural environments has also been found to increase positive and self-transcendent emotions such as awe (Sturm et al, 2020), peak experiences (Wulff and Maslow, 1965) and the perception feeling worthwhile (White et al, 2017).…”
Section: Connecting To Naturementioning
confidence: 99%
“…The experience of awe has been linked to enhanced well-being ( Anderson et al, 2018b ; Dong and Ni, 2019 ; Rudd et al, 2012 ), life satisfaction ( Rudd et al, 2012 ), prosociality ( Bai et al., 2017 ; Piff et al, 2015 ; Sturm et al, 2020 ), and reduced negative affect ( Lopes et al, 2020 ), and mental distress ( Sturm et al, 2020 ), in addition to being associated with nature relatedness ( Bethelmy and Corraliza, 2019 ) and pro-environmental behaviour ( Wang and Liu, 2019 ; Zhao et al, 2018 ), all enduring effects associated with psychedelic use ( Gandy, 2019 ). Psychedelics have been found to elicit feelings of awe ( Griffiths et al, 2006 ; Hendricks, 2018 ; Noorani et al, 2018 ; Riba et al, 2001 ; Richards et al, 1977 ; Watts et al, 2017 ), and an enhancement of awe may persist beyond the acute experience ( Noorani et al, 2018 ).…”
Section: Potential Beneficial Synergy Of Psychedelics and Nature Contmentioning
confidence: 99%
“…It has been proposed that administering psychedelics in natural settings known to elicit awe may enhance treatment efficacy of psychedelic therapy if safety is ensured ( Hendricks, 2018 ). Experiences of awe in nature may be associated with perception of large natural objects such as mountains or vistas, events such as storms, or objects with infinite repetition, including waves and fractal patterns, such as trees, clouds, rain and birdsong – and a ‘smallness of self’ in this context ( Forsythe and Sheehy, 2011 ; Keltner and Haidt, 2003 ; Richards, 2001 ; Shiota et al, 2007 ; Sturm et al, 2020 ). Perception of fractal patterns is also commonly associated with the visual imagery elicited by psychedelics ( KlĂŒver, 1966 ; Varley et al, 2020 ).…”
Section: Potential Beneficial Synergy Of Psychedelics and Nature Contmentioning
confidence: 99%
See 1 more Smart Citation
“…"The blocking of one's capacity for wonder and the loss of the capacity to appreciate mystery can have serious effects upon our psychological health, not to mention the health of our whole planet" Rollo May, PhD. 1992 [124] Awe is a positive emotion that is typically provoked by grand stimuli (e.g., viewing scenes of the Earth from space, vast scenes of breathtaking nature, or childbirth can provoke awe); aweprovoking stimuli often present with an element of mystery and wonder; a scene or event that is not immediately understood [125,126]-perhaps indistinct with what philosophers refer to as the sublime (Figure 7) [127]. Awe has been connected to lower systemic inflammation, emotional well-being, increased life satisfaction, mindfulness, increased patience, decreased materialism, and pro-social and pro-environmental behaviors [128][129][130][131].…”
Section: Box 2 Awe Wonder and Great Mysteries In Planetary Healthmentioning
confidence: 99%